Twenty-Year Review of a Single Surgeon's Experience Using a Unique Surgical Technique to Correct Lambdoidal Synostosis. Issue 7 (October 2017) - Rodriguez-Feo, Charles; Winocour, Julian; Ramirez, Roberto; Spear, Marcia; Kelly, Kevin
Abstract : Background: Numerous techniques for the surgical management of lambdoidal synostosis have been previously described; however, no best practice technique currently exists. Surgical procedures range from complete posterior calvarial reconstruction to distraction osteogenesis techniques. Our primary purpose is to describe a novel approach to correct unilateral or bilateral lambdoidal synostosis. Methods: A retrospective review was performed on a single surgeon's experience with craniosynostosis (1994–2014). Specifically, craniosynostosis cases involving the lambdoidal suture, which were repaired using a novel 'tongue and groove' technique, were identified. Results: A total of 664 craniosynostosis cases were retrieved, with 21 primarily involving the lambdoidal suture (3.2%). Of these, 18 were unilateral and 3 were bilateral lambdoidal synostosis. Male-to-female ratio was 3:1. Average age of first encounter with a craniofacial physician was 33 weeks (8 months). Average age at time of surgery was 43 weeks (10.75 months). Complications of this technique included 1 patient who experienced refusion of his lambdoidal suture and fusion of his sagittal suture, and 4 who returned for bone graft coverage of full-thickness calvarial defects owing to a lack of complete reossification. Conclusion: The "tongue and groove" technique represents a novel method for the management of lambdoidal synostosis with good esthetic outcomes, allowing immediate cranial stabilization with increased skull volume. This technique, used by the senior author for >20 years, provides a reproducible and reliable method of correcting lambdoidal synostosis.